Publication manual of the American Psychological Association - American Psychological Association (American Psychological Association (Verfasser), 1983)
Rules for manuscript preparation for articles in the field of psychology and other areas, but especially in the 18 American Psychological Association journals. The manual
Keywords: Anleitung; Bibliografie; Lehrbuch; Communication en psychologie; Psychologie - Art d'écrire; Psychologie; Uitgeven; Wetenschappelijke teksten; Sozialwissenschaften; Psychological literature; Psychology; Social science literature; Social sciences; Writing; Wissenschaftliches Manuskript; Norm; Satzanweisung; Edition; Wissenschaftlicher Text; Richtlinie